The Existence of Sentencing Guidelines for Bribery Crimes after the Criminal Code in Safeguarding Judicial Independence - Kristina Melati Pasaribu,; Prija Djatmika,; Yuliati, (Kertha Patrika, 2025)
This study aims to analyze the existence of regulations concerning sentencing guidelines for bribery cases in Indonesia and their influence on judicial decisions concerning the principle of judicial independence. The research employs a normative legal research method with statutory, conceptual, cases, and comparative approaches. The research findings indicate that the regulation of sentencing guidelines in Indonesia is still not specifically mandated. While the Supreme Court has issued a Supreme Court Regulation on Sentencing Guidelines for State Financial Corruption, which is limited to state financial corruption cases, no specific rules yet exist for bribery cases. Following the enactment of the National Criminal Code which takes effect in 2026, Indonesia will possess sentencing guidelines that apply to all criminal offenses, including bribery cases. This regulation appears to be general in nature in order to uphold the independence of judges when adjudicating cases. Judges are granted the authority to determine the severity or leniency of the sentence for the perpetrator by considering the standards set forth in Article 54 of the National Criminal Code, which is expected to provide rational justification in sentencing, thus achieving legal certainty.
Keywords: Corruption; Bribery; Sentence